2407. Overexpression of Virulence Factors in Biofilm from Recurrent Clostridium (Clostridioides) difficile Infection Isolates. - Tijerina, Laura (Open Forum Infect Dis, 2019)
BACKGROUND: Recurrent Clostridium (Clostridioides) difficile infection (R-CDI) remains a significant healthcare problem. Our aim was to analyze virulence/colonization determinants including spore formation, and expression of quorum sensing factors and adhesion capability in C. difficile biofilms, which serve as a potential reservoir for C. difficile in R-CDI. METHODS: Isolates obtained from patients with R-CDI (n = 39) and non-recurrent CDI (NR-CDI) (n = 93) were analyzed. Isolates were identified by PCR and MALDI-TOF MS and ribotyped by 16S-RNA amplification and capillary electrophoresis. Biofilm production in a C. difficile and in a C. difficile-microbiota (Enterococcus and Lactobacillus species) model was assessed by the crystal violet method. Spore counts were determined both in planktonic and biofilm growth. RNA was extracted from a selection of strains from R-CDI (n = 10) and NR-CDI (n = 10) isolate biofilms and relative expression levels of: spo0A, sigH, slpA, cwp84, agrD1 and luxS were determined. RESULTS: All NR-CDI and R-CDI isolates were biofilm producers and most were strongly adherent (90.90%) and 027 ribotype (81.37%). In the C. difficile biofilm model, spore formation was higher in R-CDI than in the NR-CDI isolates (P = 0.015). In the biofilm of C. difficile-microbiota, no difference was detected in spore formation between the R-CDI and NR-CDI isolates (P = 0.677). Expression of sigH (p = 0.007), spo0A (p = 0.003), cwp84 (p = 0.001) and agrD1 (p = 0.001) was higher in R-CDI than NR-CDI isolates. No difference was shown in slpA (p = 0.066) and luxS (p = 0.400) expression between groups. CONCLUSION: Our data suggest that expression of sporulating pathway genes, sigH, spo0A, the quorum sensing gene, agrD(1); and adhesion-associated gene, cwp84 is higher in R-CDI isolates, in addition to elevated spore formation, which may have an impact on the recurrence of the infection. DISCLOSURES: All authors: No reported disclosures.